Rheological behavior of fly ash suspension with additive for hydraulic conveyance - Kumar, Kaushal (Zielona Góra: Uniwersytet Zielonogórski)
In the present work, rheological behaviour of a fine particulate fly ash slurry suspension is studied with and without addition of an additive. Rheological experiments are performed for the range of shear rate from 50 to 200 s1. Sodium sulfate is used as an additive in the fraction of 0.2, 0.4 and 0.6% (by weight). Addition of sodium sulfate to the fly ash slurry suspension leads to an improvement of its rheological characteristics.
Keywords: fly ash; rheology; relative viscosity; pressure drop; energy consumption